Arts vs Engineering: The Choice among Consumption of and Investment in Education - Richard Romano; Alessandro Tampieri (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
In this paper we develop a model in which students choose their university coursework based on both investment and consumption incentives. We show that these education decisions are socially inefficient. This result is driven by the fact that students do not consider an externality in the working environment of acquiring education for investment purposes. We show when and how it is possible to design tuition fees in such a way that students acquire the socially optimal level of education.
Keywords: D62; H21; I21; 330